Association between irregular daily routine and risk of incident stroke and coronary heart disease in a large Japanese population - Takahiro Yoshizaki; Junko Ishihara; Ayaka Kotemori; Yoshihiro Kokubo; Isao Saito; Hiroshi Yatsuya; Kazumasa Yamagishi; Norie Sawada; Motoki Iwasaki; Hiroyasu Iso; Shoichiro Tsugane; The JPHC Study Group (Scientific Reports, 2022)
Abstract Circadian misalignments have been linked to adverse cardiometabolic outcomes. However, the association between irregular daily routine and the risk of cardiovascular disease (CVD) remains unknown. We examined this association in a prospective study in Japan. The study included 78,115 Japanese participants aged 45–74 years. The self-reported daily routine was evaluated using the question, ‘Is your daily routine or activity schedule regular?’ The response (yes/no) was obtained as a binary variable. Cox proportional hazard regression analysis was used to estimate the hazard ratios and 95% confidence intervals for the association between an irregular daily routine and CVD incidence risk. Among the participants, 23.7% reported an irregular daily routine. During the mean follow-up period of 13.3 years, we observed 4641 CVD events. An irregular daily routine was significantly associated with increased risks of CVD and total stroke in women, but not in men. This positive association between an irregular daily routine and the risk of CVD was weak in the high vegetable and fruit consuming population. An irregular daily routine is positively associated with the risk of incident CVD, especially in women. These associations may be weak in populations that consume a diet rich in vegetables and fruits.